Basaloid Squamous Cell Carcinoma of the Head and Neck: Subclassification into Basal, Ductal, and Mixed Subtypes Based on Comparison of Clinico-pathologic Features and Expression of p53, Cyclin D1, Epidermal Growth Factor Receptor, p16, and Human Papillomavirus - Cho, Kyung-Ja; Jeong, Se Un; Kim, Sung Bae; Lee, Sang-wook; Choi, Seung-Ho; Nam, Soon Yuhl; Kim, Sang Yoon (Journal of pathology and translational medicine, 2017)
Basaloid squamous cell carcinoma (BSCC) is a rare variant of squamous cell carcinoma with distinct pathologic characteristics. The histogenesis of BSCC is not fully understood, and the cancer has been suggested to originate from a totipotent primitive cell in the basal cell layer of the surface epithelium or in the proximal duct of secretory glands. Twenty-six cases of head and neck BSCC from Asan Medical Center, Seoul, Korea, reported during a 14-year-period were subclassified into basal, ductal, and mixed subtypes according to the expression of basal (cytokeratin [CK] 5/6, p63) or ductal markers (CK7, CK8/18). The cases were also subject to immunohistochemical study for CK19, p53, cyclin D1, epidermal growth factor receptor (EGFR), and p16 and to hybridization for human papillomavirus (HPV), and the results were clinico-pathologically compared. Mixed subtype (12 cases) was the most common, and these cases showed hypopharyngeal predilection, older age, and higher expression of CK19, p53, and EGFR than other subtypes. The basal subtype (nine cases) showed frequent comedo-necrosis and high expression of cyclin D1. The ductal subtype (five cases) showed the lowest expression of p53, cyclin D1, and EGFR. A small number of p16- and/or HPV-positive cases were not restricted to one subtype. BSCC was the cause of death in 19 patients, and the average follow-up period for all patients was 79.5 months. Overall survival among the three subtypes was not significantly different. The results of this study suggest a heterogeneous pathogenesis of head and neck BSCC. Each subtype showed variable histology and immunoprofiles, although the clinical implication of heterogeneity was not determined in this study.